Answers

2016-04-07T15:44:15+05:30
 1)  If x = 1,
     -48(1)+6y+24= 0
       6y= 48-24
       6y= 24
       y= 4
2)    if x= 2
         -48(2)+6y+24=0
         -56+6y+24=0
           6y=56-24
           6y= 32
              y= 6
3) if x= -1
       -48(-1)+6y+24= 0
         48+6y+24=0
           6y= -48-24
           6y= -72
             y= -12
4) if x=-2
       -48(-2) +6y+24=0
         96+6y+24=0
           6y= -96-24
           6 y=-120
               y =-20
therefore, the four solutions are (1,4) ; (2,6); (-1,-12) ; (-2,-20)

          



0